Psychiatric sequelae of traumatic brain injury (TBI) - Ghosh, Ambarish; Desai, Birva; Halder, Arghya; Ghosh, Aniruddha; Das, Priyanka; Saldanha, Daniel (Asian Journal of Medical Sciences, 2020)
Background: Traumatic brain injury (TBI), a leading cause of morbidity and mortality worldwide, is an alteration in brain function, caused by an external force. With rapid surge in urbanization, motorization and economic liberalization in India, risk of TBI is increased, raising a cause for concern about its neurological as well as psychiatric sequelae. Aims and Objectives: This study was planned to understand the magnitude of the problem which could give us insights to manage/ rehabilitate it in a more comprehensive manner. Materials and Methods: The current study included 50 patients aged 18-60 years at DY Patil Medical College, Pune. GCS scores were noted for severity of TBI. Patients were assessed through MMSE, BCRS, HAM-A & BDI. Results: On GCS, 20% cases had severe head injury; 22% moderate and 58% had mild. On MMSE initially, at six months and one year; 26.19%, 21.88% & 11.1% cases had cognitive impairment respectively. On BCRS, 38.10%, 34.4% & 37.10% cases had cognitive deterioration initially, at six month & at one year respectively. On HAM-A, mild & moderate to severe anxiety was found in 64.3% & 35.7% cases respectively. On BDI, initially 7.14% cases had depression, 25% at six months and 37.05% after one year. No statistically significant change was seen in BCRS score during follow up. Comparison of the mean scores at first interview and at six months demonstrated statistically significant (P-value p<0.005) differences in MMSE as well as BDI. Conclusion: TBI is associated with n increased risk of psychiatric disorders and may need psychiatric interventions later.